2017
DOI: 10.1055/s-0037-1612637
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in the Prevalence of Common Orthopaedic Upper Extremity Conditions

Abstract: Seasonal variation in disease processes and injuries have been reported, but it is unclear if this variation exists in upper extremity disorders. The goal of this study is to characterize seasonal and weather variations in common upper extremity orthopaedic conditions. This cross-sectional study reviewed 68,943 consecutive, new patient visits from January 2010 to September 2015 for carpal tunnel syndrome (CTS), trigger finger (TF), DeQuervain's tenosynovitis (DeQ), lateral epicondylitis (LE), hand arthritis (O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The same time period was chosen for 2019 to reduce the impact of seasonal variation on case volume. 14 , 15 All surgeries were performed by fellowship-trained orthopedic spine surgeons. All patients met the 30-day follow-up required for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same time period was chosen for 2019 to reduce the impact of seasonal variation on case volume. 14 , 15 All surgeries were performed by fellowship-trained orthopedic spine surgeons. All patients met the 30-day follow-up required for inclusion in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The World Health Organization officially declared COVID-19 a pandemic on March 11, 2020, 13 and many institutional policies had been set in place by July 1, 2020. The same time period was chosen for 2019 to reduce the impact of seasonal variation on case volume 14,15 . All surgeries were performed by fellowship-trained orthopedic spine surgeons.…”
Section: Methodsmentioning
confidence: 99%
“…The survey indicated that DRFs were more common during warm seasons (summer and autumn). However, Warrender WJ [ 25 ] found that the incidence of DRFs is significantly higher during the winter season compared to other seasons, likely due to the presence of slippery road surfaces during winter months. Johnson NA et al [ 26 ] also found that in cold weather, the incidence of DRFs was significantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the incidence of distal radius fracture was the highest in summer and autumn, with obvious seasonality. Warrender WJ (19) found that the incidence of distal radius fracture was signi cantly higher in winter than in other seasons, and the reason was related to the slippery road surface with snow and ice in winter, which was more likely to be injured.Johnson NA et al (20) found that in cold weather, the incidence of distal radius fracture was signi cantly increased; Ogliari et al (21) found that ulnar, radius and humerus fractures peaked in December and winter, and the number of frost days was directly related to them. The results of this study are contradicted by the literature reporting that Stotz A et al (22) showed that high ambient temperature reduces blood pressure in young and middleaged adults and may lead to orthostatic hypotension, increasing the risk of falls and fall-related fractures in older adults; Secondly, the increase of outdoor exercise in summer and less travel in winter may be the reasons for the lower incidence of distal radius fractures in winter, and it may also be due to slippery roads in rainy season, that is more rain in summer and autumn in east China.…”
Section: Seasonal Variation Of Distal Radius Fractures In East Chinamentioning
confidence: 99%